Mapping Intellectual Structure of Financial Accounting Research: A Scientometric Review Using VOSviewer - Judijanto, Loso (Westscience Press, 2025)
This study delineates the intellectual framework of financial accounting research using a scientometric analysis employing VOSviewer. It looks at keyword co-occurrence, co-authorship, institutional affiliations, and nation collaboration networks using papers indexed in Scopus from 2000 to 2024. The results suggest that accounting, finance, and corporate governance are the most important parts of the area. There are also dense groups of topics on financial reporting, earnings management, capital structure, and financial performance. Overlay and density visualizations show that concepts like sustainability, sustainable development, and risk assessment are becoming more popular over time. Co-authorship and nation maps show that the US and China are the most powerful countries, but Australia, European countries, and several Asian economies play major roles in connecting them. The study provides pragmatic recommendations for policymakers and academics in pinpointing established domains, nascent subjects, and prospective collaborations, while also recognizing constraints associated with database scope and dependence on citation-based metrics.